The peculiarities of utilizing testers different genetical structure for breeding precocious corn hybrids (Zea mays L.). - О. С. Макарчук; В. Л. Жемойда (Plant Varieties Studying and Protection)
The possibilities of utilizing testers different genetical structure are considered. The peculiarities of testers productivity formation are ascertained. The dynamics of influence inbreed lines, testers and one's interaction on hybrids productivity are investigated. The peculiarities of hybrids productivity formation depending on utilizing testers and one's combining are indicated.